Visual outcome and complications of manual small incision cataract Surgery (MSICS) in a peripheral CMH (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Manual small incision cataract surgery (MSICS) is a cost-effective alternative to phacoemulsification cataract surgery for developing countries. This prospective study was carried out in Combined Military Hospital (CMH), Chittagong from October 2009 to March 2011 on 75 cataract patients who were operated by MSICS technique. Objectives: Aim of this study was to assess the visual outcome and complications of MSICS in a peripheral CMH. Methods: Seventy five cataract patients were operated by MSICS technique. All surgical procedures were performed by the principal author. Major per-operative and postoperative complications were documented. Visual outcome was assessed by Snellens visual acuity test 06 weeks after operation. Results: Uncorrected visual acuity (UCVA) was 6/6 6/18 in 57 (76.0%) patients, < 6/18 6/60 in 15 (20%) and < 6/60 in 03 (4.0%) patients. Best corrected visual acuity (BCVA) was 6/6-6/18 in 65 (86.7%) patients, < 6/18-6/60 in 07 (9.3%) and < 6/60 in 03(4.0%) patients. Visual outcome was good in 86.7% of patients according to World Health Orgnization (WHO) criteria and was not far away from the WHO expected outcome. Posterior capsule rupture was the most significant per-operative complication which was found in 7(9.3%) cases and surgically induced astigmatism was main postoperative complication that affected visual outcome. Mean postoperative astigmatism (against-the rule) was - 1.25DC. 14 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 Conclusion: MSICS is a safe and cost-effective technique of extra-capsular cataract extraction where surgical skill and experience of the surgeon plays a significant role in the result. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22895 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014